Late Permian-earliest Triassic high-resolution organic carbon isotope and palynofacies records from Kap Stosch (East Greenland) - Sanson-Barrera, Anna; Hochuli, Peter A.; Bucher, Hugo; Schneebeli-Hermann, Elke; Weissert, Helmut; Adatte, Thierry; Bernasconi, Stefano M.; id_orcid:0 000-0001-7672-8856 (Global and Planetary Change, 2015)
ISSN:0921-8181